Analysis of Wildfire Visualization Systems for Research and Training: Are They Up for the Challenge of the Current State of Wildfires? - Cortes, Carlos A. Tirado; Thurow, Susanne; Ong, Alex; Sharples, Jason J.; Bednarz, Tomasz; Stevens, Grant; Favero, Dennis Del (IEEE transactions on visualization and computer graphics, 2024)
Wildfires affect many regions across the world. The accelerated progression of global warming has amplified their frequency and scale, deepening their impact on human life, the economy, and the environment. The temperature rise has been driving wildfires to behave unpredictably compared to those previously observed, challenging researchers and fire management agencies to understand the factors behind this behavioral change. Furthermore, this change has rendered fire personnel training outdated and lost its ability to adequately prepare personnel to respond to these new fires. Immersive visualization can play a key role in tackling the growing issue of wildfires. Therefore, this survey reviews various studies that use immersive and non-immersive data visualization techniques to depict wildfire behavior and train first responders and planners. This paper identifies the most useful characteristics of these systems. While these studies support knowledge creation for certain situations, there is still scope to comprehensively improve immersive systems to address the unforeseen dynamics of wildfires.